2022
DOI: 10.1021/acs.est.2c00813
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Patterns of Antimicrobial Resistance Genes in the US EPA National Rivers and Streams Assessment Survey

Abstract: Antimicrobial resistance (AR) is a serious global problem due to the overuse of antimicrobials in human, animal, and agriculture sectors. There is intense research to control the dissemination of AR, but little is known regarding the environmental drivers influencing its spread. Although AR genes (ARGs) are detected in many different environments, the risk associated with the spread of these genes to microbial pathogens is unknown. Recreational microbial exposure risks are likely to be greater in water bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Importantly, human and bovine fecal contamination of these wells was associated with estimates of significant health risk (Burch et al, 2021). Therefore, while intI1 may indicate abundant fecal contamination or aggregated fecal influence (Beattie et al, 2018;Bourdonnais et al, 2022;Kampouris et al, 2021;Keely et al, 2022;Lee et al, 2021), our results suggest that it may not accurately predict contamination in all settings, like rural areas with dispersed septic systems and variable manure inputs.…”
Section: Land Use Risk Factors For Arg and Inti1 Contamination Of Pri...mentioning
confidence: 78%
“…Importantly, human and bovine fecal contamination of these wells was associated with estimates of significant health risk (Burch et al, 2021). Therefore, while intI1 may indicate abundant fecal contamination or aggregated fecal influence (Beattie et al, 2018;Bourdonnais et al, 2022;Kampouris et al, 2021;Keely et al, 2022;Lee et al, 2021), our results suggest that it may not accurately predict contamination in all settings, like rural areas with dispersed septic systems and variable manure inputs.…”
Section: Land Use Risk Factors For Arg and Inti1 Contamination Of Pri...mentioning
confidence: 78%
“…A similar pattern was observed at the sites with acid mine drainage impacts (sites 1, 2, and 5), where sul1 and mexE were detected without MST markers. One possible explanation for the persistent detection of ARGs is the potential role of 27,61 Researchers found that ARGs had an increased potential for mobility in samples collected downstream of wastewater discharges relative to upstream, supporting the elevated potential for the transfer of ARGs in a similar environment. 3) and statistical relationships (e.g., the significant and positive correlation between FIB E. coli and anthropogenic ARGs) (Figure 4) suggest that E. coli contamination could be useful for predicting ARGs in surface water.…”
Section: Arg Prevalence Investigation and Args Abundance In Surface W...mentioning
confidence: 99%
“…To complement the surveys in human and animal sectors under the “One-Health” framework, surveillance has been increasingly conducted in environmental sectors, including manure, soil, freshwater, , marine water, and wastewater treatment plants. Conventional cultivation-based methods for characterizing ARB provide comprehensive information in terms of ARB phylogeny, resistance phenotype, and transferability of the resistance determinants. However, cultivation is highly exhaustive, and frequently only a small fraction of environmental bacteria can be cultivated.…”
Section: Introductionmentioning
confidence: 99%